Heterostructured bimetallic–sulfide@layered Ti3C2Tx–MXene as a synergistic electrode to realize high-energy-density aqueous hybrid-supercapacitor. (October 2022) - Javed, Muhammad Sufyan; Zhang, Xiaofeng; Ali, Salamat; Mateen, Abdul; Idrees, Muhammad; Sajjad, Muhammad; Batool, Saima; Ahmad, Awais; Imran, Muhammad; Najam, Tayyaba; Han, Weihua
Abstract: Aqueous hybrid supercapacitors (AHSCs) exhibit promising electrochemical performance with long cyclic stability and high power density. However, the low-energy density restricted their development to commercialization. To improve the energy density, we proposed a heterostructured (HS) composite of nickel–cobalt–sulfide (NCS) nanoflowers embedded in exfoliated Ti3 C2 T x −MXene layers (HS−NCS@MXene). The NCS nanoflowers were uniformly dispersed inside the MXene layers and formed a sandwich-like structure. The HS−NCS@MXene exhibited remarkable pseudocapacitive performance in a three-electrode system. The capacitance can reach 2637 F g −1 (1582 C g −1 ) at 2.5 A g −1 with stable cycling life over 10, 000 cycles and retained 96% capacity of the initial value. Post−mortem investigations confirmed that the charge storage mechanism in HS−NCS@MXene composite is a combination of Faradic and electrochemical double-layer storage. An AHSC was assembled by coupling the HS−NCS@MXene as a positive electrode and activated carbon as a negative electrode (HS−NCS@MXene//AC–AHSC). The HS−NCS@MXene//AC–AHSC can operate in a potential range up to 1.6 V and deliver a high capacitance of 226 F g −1 at 1.5 A g −1 with stable cyclic life (92%) up to 20, 000 cycles. Moreover, the HS−NCS@MXene//AC−AHSC also possessed a high energy density of 80 Wh kg −1 at a power density of 1196 W kg −1, which exceeds most recently published works. The synergistic effect of NCS and MXene enables the HS−NCS@MXene composite to deliver outstanding electrochemical performance for AHSCs. Graphical Abstract: To realize highly efficient aqueous hybrid supercapacitor, HS−NCS@MXene electrode with multi-component and rational morphological architectures is proposed. The HS−NCS@MXene electrode demonstrates remarkable pseudocapacitive performance in a three- and two electrode systems with reduced ionic diffusion paths. ga1 Highlights: Nickel-cobalt-sulfide-nanoflowers in-situ embedded in Ti3 C2 Tx –MXene layers to construct heterostructured electrode. The HS–NCS@MXene electrode exhibits exceptional high–capacitance of 2637 F g –1 at 2.5 A g –1 with superb rate-capability. The HS–NCS@MXene//AC-AHSC shows good performance by achieving a high capacitance of 226 F g –1 at 1.5 A g –1 . The HC–NCS@MXene//AC–AHSC delivers high-energy/power densities (80 Whkg –1 @ 1196 Wkg –1 ) super-long life up to 20k cycles.